Pelatihan Penulisan Artikel Ilmiah untuk Guru Bahasa Indonesia Sekolah Menengah Kejuruan di Kabupaten Karanganyar Jawa Tengah - Susanto, Dwi (LPPPM STAI Darul Hikmah Bangkalan, 2023)
This service activity is based on the needs of Indonesian language teachers at vocational high schools in Karanganyar Regency, Central Java, for writing scientific articles for accredited national journals. This activity is in the form of technical training in writing scientific articles, knowledge about nationally accredited journals, and how to submit them to national journals. Forty-three teachers participated in this activity. This activity is in the form of lectures or giving material, practice opening the Open Journal System page. Activities went well, especially when giving material to make abstracts, introductions, and research methods. In the question and answer session or discussion, participants raised various issues such as writing using the Mendeley application and how to change action research reports into scientific articles. These two problems arose during the training so the solution provided was mentoring and further training was held on this matter